Genome‐wide characterization of aquaporins in Spirodela polyrhiza and expression of aquaporin gene family under high‐temperature stress. Issue 9 (26th August 2022) - Shang, Shuai; Zhang, Zaiwang; Liu, Xiaoxue; Liu, Longxiang; Tang, Xuexi
Abstract : As one of the most conserved classes of gene families, aquaporins (AQP) genes play an essential role in water transport and stress resistance in organisms. However, little information was available for their evolutionary and functional roles in aquatic plant species. In the present study, gene sequences, gene structure, phylogeny, conserved motif and promoter of the AQP genes in Spirodela polyrhiza were investigated to explore the mechanisms of osmoregulation underwater. A total of 24 putative AQP genes divided into four clades representing four distinct AQPs subfamilies were identified. The gene structure and intron numbers of the AQP genes were conserved among subfamilies. The Froger's residues, conserved Ar/R selectivity filters and conserved NPA domain showed high differences among different subfamilies. Moreover, the promoter profiling of SpAQP genes for conserved cis‐acting regulatory elements revealed enrichment of cis‐elements involved in light response and stress responsiveness, reflecting their varying gene expression pattern. Our results demonstrated that the AQP genes in the S. polyrhiza were similar to those in the Zostera marina and might have experienced adaptive evolution to water. Transcriptome results showed that the SpTIP2‐3, SpPIP2‐2, SpPIP1‐3, SpTIP4‐3 and SpNIP5‐2 were expressed significantly among different treatments indicating they might play important roles under temperature stress. These data offer valuable sight into understanding the adaptation to the water of the S. polyrhiza . They may further inform our understanding of the evolution of water tolerance in S. polyrhiza .